2015
DOI: 10.4049/jimmunol.1402417
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Death Ligand 1 on Burkholderia pseudomallei–Infected Human Polymorphonuclear Neutrophils Impairs T Cell Functions

Abstract: Polymorphonuclear neutrophils (PMNs) are terminally differentiated cells that are involved in innate immune responses and form an early line of defense against pathogens. More recently, it has been shown that PMNs have immunosuppressive abilities on other immune cells. However, the effect of PMNs on T cell responses during bacterial infection remains to be determined. In this report, we examined the interaction of PMNs and T cells in response to infection with Burkholderia pseudomallei, the causative agent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 42 publications
(58 reference statements)
2
26
0
Order By: Relevance
“…These neutrophils suppress T cell function via PD-L1/PD-1 interaction and production of ROS [89]. The same suppressive function was also observed in Burkholderia pseudomallei infected neutrophils, that up-regulated expression of PD-L1 and was able to inhibit CD4 + T cell proliferation and IFN-γ production in response to polyclonal activators, mediated by the PD-L1/PD-1 pathway [90].…”
Section: T Cell Activities Under Neutrophils Controlsupporting
confidence: 54%
“…These neutrophils suppress T cell function via PD-L1/PD-1 interaction and production of ROS [89]. The same suppressive function was also observed in Burkholderia pseudomallei infected neutrophils, that up-regulated expression of PD-L1 and was able to inhibit CD4 + T cell proliferation and IFN-γ production in response to polyclonal activators, mediated by the PD-L1/PD-1 pathway [90].…”
Section: T Cell Activities Under Neutrophils Controlsupporting
confidence: 54%
“…In addition, the exhausted CD8+ T cell population also expressed inhibitor receptors, such as PD-1 and lymphocyte activation gene 3. In an in vitro study on the effect of B. pseudomallei K96243 on human polymorphonuclear neutrophils (PMNs) and CD4+ T cell function, it was found that there was a greater inhibition of T cell functions (proliferation and IFN-γ expression) by infected B. pseudomallei PMNs than by uninfected PMNs [60]. It was also reported that T cell suppression caused by infected PMNs was mediated by the programmed death 1 (PD-1)/programmed death ligand-1 (PD-L1) pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Another crucial issue is that the definition of ‘immunosuppressive’ must rely on the demonstrated capacity to suppress T‐cell responses (such as proliferation and/or IFN‐ γ production) by neutrophils . The inhibition of T‐cell responses by human immunosuppressive neutrophils primarily occurs through an overproduction of ARG‐1, ROS, or via PD‐L1‐dependent interactions . Polarization of T‐helper cell responses towards an anti‐inflammatory phenotype (expansion of Th2 and Treg cells and inhibition of Th1 cells) has also been proposed as an immunosuppressive mechanism used by human LDNs/PMN‐MDSCs .…”
Section: Neutrophils and T Cellsmentioning
confidence: 99%